Morphological and Histological Comparative Study between the Lower Respiratory System of Pigeon (Columba livia) and Guinea Pig (Cavia porcellus) - mahmood rajab, jehan; Abdulmahdi Mohsin, Raghad; Saadi Mohammed, Nagham (Medical Science Journal for Advance Research, 2024)
The current study showed that there are morphological and anatomical differences between pigeons and guinea pigs. The trachea appeared in pigeons in the form of a long tube containing cartilaginous rings that were completely round and overlapping with each other, while the trachea appeared in the guinea pig in the form of a long tube with a diameter wider than that of the pigeon. It consisted of a group of cartilaginous rings that were not completely round. In both types, the lung consisted of left and right lobes. The lung in pigeons was rectangular in shape, fragile, and it has many blood vessels, it was closely attached to the ribs. The lung of the guinea pig was composed of a group of lobes pyramidal in shape, and the left lung was smaller than the right lung. Histologically, the trachea in both animals consisted of four tissue layers, which are mucosa, submucosa, and a layer of connective tissue that contains cartilage and is covered from the outside with a layer of covering tissue called the adventitia. The lung in the pigeons also consisted of connective tissue with wide holes that were uniformly distributed throughout the lung tissue. The lung in the guinea pig consists of connective tissue with many branches, which represent the branches of the bronchioles, and those branches end with air sacs in the form of clusters. The differences in the nature of the behavior of the two animals could be a major reason for the presence of morphological and histological differences in the structure of the respiratory system of both animals.